The effectiveness of convalescent plasma and hyperimmune immunoglobulin for the treatment of severe acute respiratory infections of viral etiology: a systematic review - Mair-Jenkins, John; Saavedra-Campos, Maria; Baillie, J. Kenneth; Cleary, Paul; Khaw, Fu-Meng; Lim, Wei Shen; Makki, Sophia; Rooney, Kevin D; Beck, Charles R.; Nguyen-Van-Tam, Jonathan S. (Oxford University Press, 2014)
Background: Administration of convalescent plasma, serum, or hyperimmune immunoglobulin may be of clinical benefit for treatment of severe acute respiratory infections (SARIs) of viral etiology. We conducted a systematic review and exploratory meta-analysis to assess the overall evidence.